Isolation and characterization of novel phages in treating multidrug resistant Klebsiella pneumoniae using zebrafish larvae model - Assafiri, Omar (2020)
As time progresses, Klebsiella pneumoniae is becoming more resistant to antibiotics, thus rendering them ineffective. Phages have the potential to replace the antibiotics. In this study, two phages, Klebsiella virus UPM2146 and UPM1705, which were able to lyse K. pneumoniae ATCC BAA-2146 and ATCC BAA-1705, respectively were isolated from a polluted lake. These phages had a titer of 1012 PFU/ml and 107 PFU/ml, respectively. Transmission electron micrographs showed that both phages belong to the order Caudoviriales. Klebsiella virus UPM2146 had an adsorption period of 2 min, a latent period of 20 min, a rise period of 5 min, and a burst size of 20 PFU/bacteria. UPM1705 had an adsorption period of 2 min, a latent period of 75 min, a rise period of 45 min, and a burst size of 298 PFU/bacteria. Turbidity assay at multiplicities-of-infection (MOI) of 0.02, 0.2, and 2 indicated that Klebsiella virus UPM2146 and UPM1705 were able to lyse their hosts at 60 min and 180 min, respectively. Furthermore, spot and efficiency-ofplating (EOP) tests indicated that Klebsiella virus UPM2146 had a narrow host-range lysing 22.72% of the K. pneumoniae species tested but UPM1705 was only specific to its host. Klebsiella virus UPM2146 was selected for further analyses. Whole genomic sequencing revealed that Klebsiella virus UPM2146 has a double-stranded DNA genome of 160,795 bp with 214 putative open-reading-frames (ORF). Klebsiella virus UPM2146 is lytic, and lacking toxin and integrase genes. Phylogenetic tree analysis classified Klebsiella virus UPM2146 within the new Ackermannviridae family. The zebrafish larvae model was used to test the efficacy of Klebsiella virus UPM2146 in lysing K. pneumoniae ATCC BAA-2146. The larvae were able to survive up to 24 hours after 30 min exposure to the host bacteria. The appearance of a curved spine resembling a hook indicated dead larvae. Upon treatment with Klebsiella virus UPM2146, the zebrafish larvae was able to survive up to 10 hours. Therefore, Klebsiella virus UPM2146 has the potential to be used in phage therapy.